La propaganda política en las elecciones presidenciales venezolanas del 2006: estudio de las estrategias de argumentación - Alberto Morales, Oscar; Ilich Marín-altuve, Ernesto; González-peña, Carolina (Estudios sobre el Mensaje Periodístico, 2008)
The aim of this paper is to describe and to analyze the communicative strategies used in the political campaign of the Venezuelan presidential elections in 2006. We analyzed a corpus of 420 electoral ads published in four Venezuelan newspapers during the electoral campaign between August and December 2006. Data were analyzed qualitatively. We found that Chavez’s ads proposes possible worlds (PW) inhabited by facts, truths and presuppositions, connected by means of argumentative strategies of link. Manuel Rosales’ proposes opposite possible worlds: it represents Chavez’s government as a negative one, characterized by hatred, corruption, division, and proposes future MP+ of well-being without him. We conclude that the works of government carried out by the candidates, considered good but incomplete, have a fundamental role for the construction and connection of the possible worlds and for the argumentation.
Keywords: Augmentative Strategies; Possible worlds; Venezuelan political discourse; Electoral campaign; Presidential elections 2006